Acute Effects of Combination Dynamic Stretching and Warming Up on Functional Performance in Non-Athlete - Salsabila Zahroh; Lydia Arfianti; Arni Kusuma Dewi; Qarib, Mohammad Fathul; Sofiatun (Surabaya Physical Medicine and Rehabilitation Journal, 2024)
Abstract Background: Warming up is an activity carried out before exercise or competition to optimize performance. Dynamic stretching is a type of stretching that is applied as a part of warming up. Previous study showed that dynamic stretching had an acute effect on functional performance in athletes. But, acute effects on functional performance in non athletes have not been studied yet. Aim: To prove that the addition of dynamic stretching during warming up has an acute effect on functional performance. Material and Methods: This study uses an experimental method of randomized controlled trial post test design on 44 physically active young adults in non athlete level who were divided into two research groups. The intervention group completed 5 minute jogging and dynamic stretching whereas the control group completed 5 minute jogging without stretching then each group performed a modified 20-m sprint run test and triple hop for distance test. Result: There is no statistical significant difference in comparison between groups. On speed showed that p values = 0.845 (p> 0.05) and on power showed that p values = 0.366 (p>0.05). Conclusion: Addition of dynamic stretching during warming up has not been proven to have a better acute effect on speed and power in non-athlete young adults.Keywords: Dynamic Stretching, Functional Performance, Warming Up